2009
DOI: 10.1016/j.immuni.2008.11.006
|View full text |Cite
|
Sign up to set email alerts
|

The Phagosomal Proteome in Interferon-γ-Activated Macrophages

Abstract: The ability of macrophages to clear pathogens and elicit a sustained immune response is regulated by various cytokines, including interferon-gamma (IFN-gamma). To investigate the molecular mechanisms by which IFN-gamma modulates phagosome functions, we profiled the changes in composition, abundance, and phosphorylation of phagosome proteins in resting and activated macrophages by using quantitative proteomics and bioinformatics approaches. We identified 2415 phagosome proteins together with 2975 unique phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
267
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 206 publications
(282 citation statements)
references
References 59 publications
12
267
0
1
Order By: Relevance
“…Indeed, characterization of the phagosome phosphoproteome and molecular analysis of the evolution of phagosomes highlighted the importance of phosphorylation in the regulation of phagolysosome biogenesis (4,12,22). This process is accomplished through transient, highly regulated interactions between the phagosome and the cytoskeleton, as well as the early, late, and recycling endocytic compartments (46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, characterization of the phagosome phosphoproteome and molecular analysis of the evolution of phagosomes highlighted the importance of phosphorylation in the regulation of phagolysosome biogenesis (4,12,22). This process is accomplished through transient, highly regulated interactions between the phagosome and the cytoskeleton, as well as the early, late, and recycling endocytic compartments (46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…In metazoans, the multiple possible combinations of these modules illustrate the complexity of phosphotyrosine signaling, which can regulate cellular functions either positively or negatively. A recent large-scale quantitative proteomic and phosphoproteomic analysis revealed that Tyr phosphorylation sites are overrepresented in phagosomes (12), as compared with global phosphoproteome (13). This finding suggested that Tyr phosphorylation plays an important role in phagosome signaling.…”
mentioning
confidence: 99%
“…PKC : A recent phosphoproteomics study of Interferon-gamma treated mouse macrophages has revealed a two-fold decrease in abundance of PKC over a 24 hour period [99]. Furthermore, this decrease in protein abundance was paralleled by dephosphorylation at Ser-317 (11-fold downregulation) and Tyr-676 (3-fold downregulation).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…In recent years, the cell line has also been used extensively in proteomics experiments including a large‐scale proteome 10, phagosome proteomics 4, 8, 11, responses to cytokines 12, 13, and identification of DNA receptors 14.…”
mentioning
confidence: 99%
“…Phagocytosis was induced for 30 min using carboxylated 1 μm polystyrene beads (Estapor/EMD Millipore) and phagosomes were isolated using sucrose ultracentrifugation in which the phagosomes float above cell debris and other organelles 11, 20. Protein extracts from three biological replicates were resuspended in 1% sodium 3‐[(2‐methyl‐2‐undecyl‐1,3‐dioxolan‐4‐yl)methoxy]‐1‐propanesulfonate (commercially available as RapiGest, Waters) in 50 mM Tris‐HCl pH 8.0 with 5 mM tris(2‐carboxyethyl)phosphine (TCEP, Pierce), heated at 60°C for 5 min, then alkylated using 10 mM iodoacetamide, diluted to 0.1% RapiGest and finally trysinized overnight at 30°C.…”
mentioning
confidence: 99%